2010
DOI: 10.1358/mf.2010.32.9.1533686
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of montelukast add-on therapy in allergic rhinitis

Abstract: Allergic rhinitis is a common airways hypersensitivity disease. Histamine and leukotrienes are involved in the pathogenesis of allergic rhinitis. Conventional treatments include topical steroids and antihistamines. Due to the adverse effects of these treatments, new drugs like leukotriene receptor antagonists are being investigated for the treatment of allergic rhinitis. A total of 90 patients suffering from allergic rhinitis were enrolled in this prospective, randomized, controlled study. Patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…The limitations of the current study are the relatively small sample size and administration of a single‐dose in healthy male volunteers. Several clinical studies have demonstrated the efficacy of Singulair ® mini in the treatment of asthma in both adults and children [8–12], and for the symptomatic relief of allergic rhinitis [13–15]. Given the bioequivalence demonstrated for the Sandoz montelukast 4 mg oral granules, this formulation is expected to be equally efficacious and well‐tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the current study are the relatively small sample size and administration of a single‐dose in healthy male volunteers. Several clinical studies have demonstrated the efficacy of Singulair ® mini in the treatment of asthma in both adults and children [8–12], and for the symptomatic relief of allergic rhinitis [13–15]. Given the bioequivalence demonstrated for the Sandoz montelukast 4 mg oral granules, this formulation is expected to be equally efficacious and well‐tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…490 One study found that montelukast add-on therapy to fluticasone nasal spray is more efficacious in controlling nighttime symptoms but similar in efficacy in controlling total symptom score. 491 With very weak evidence, suggesting on one hand a possible benefit and on the other no benefit, but with concerns for serious neuropsychiatric events from montelukast, the JTFPP suggests against the use of this combination.…”
Section: Oral Ltras With Incsmentioning
confidence: 99%
“…Several studies have proved its effectiveness in the treatment of AR. Montelukast has been shown to reduce day-time congestion, rhinorrhea, pruritus, and sneezing and improves difficulty going to sleep, night-time awakenings, and congestion on awakening [53]. It reduces the number of peripheral blood eosinophils, suggesting its antiinflammatory effect [54].…”
Section: Antileukotrienesmentioning
confidence: 99%